Lack of complex type N-glycans lessens aberrant neuronal properties. - M Kristen Hall; Douglas A Weidner; Austin A Whitman; Ruth A Schwalbe (PLoS ONE, 2018)
Modifications in surface glycans attached to proteins via N-acetylglucosamine-β1-N-asparagine linkage have been linked to tumor development and progression. These modifications include complex N-glycans with high levels of branching, fucose and sialic acid residues. Previously, we silenced Mgat2 in neuroblastoma (NB) cells, which halted the conversion of hybrid type N-glycans to complex type, to generate a novel cell line, NB_1(-Mgat2). By comparing the aberrant cell properties of the NB_1(-Mgat2) cell line to the parental cell line (NB_1), we investigated the impact of eliminating complex type N-glycans on NB cell behavior. Further, the N-glycosylation pathway in the NB_1(-Mgat2) cell line was rescued by transiently transfecting cells with Mgat2, thus creating the NB_1(-/+Mgat2) cell line. Changes in the N-glycosylation pathway were verified by enhanced binding of E-PHA and L-PHA to proteins in the rescued cell line relative to those of the NB_1(-Mgat2) cell line. Also, western blotting of total membranes from the rescued cell line ectopically expressing a voltage-gated K+ channel (Kv3.1b) revealed that N-glycans of Kv3.1b were processed to complex type. By employment of various cell lines, we demonstrated that reduction of the complex type N-glycans diminished anchorage-independent cell growth, and enhanced cell-cell interactions. Two independent cell invasion assays showed that cell invasiveness was markedly lessened by lowering the levels of complex type N-glycans while cell mobility was only slightly modified. Neurites of NB cells were shortened by the absence of complex type N-glycans. Cell proliferation was reduced in NB cells with lowered levels of complex type N-glycans which resulted from hindered progression through G1+Go phases of the cell cycle. Overall, our results illustrate that reducing the ratio of complex to hybrid types of N-glycans diminishes aberrant NB cell behavior and thereby has a suppressive effect in cell proliferation, and cell dissociation and invasion phases of NB.